Levelling up leadership: Harnessing gamification to cultivate soft skills in Italian and Portuguese master's students - Valeria Caggiano; Antonio Ragusa; Susana Moreiro Bastos (Italian Journal of Educational Technology)
This research investigates the effectiveness of gamification in enhancing leadership and teamwork abilities among Italian and Portuguese students pursuing a Master's degree in Business and Accounting Management through the "Leadership Quest" game. Employing a comprehensive data analysis methodology encompassing t-tests and ANOVA, the study assesses the game's impact on developing interpersonal skills. The results demonstrate significant enhancements in communication, strategic decision-making, and conflict-resolution skills following participation, with no discernible gender disparities. Additionally, the study delves into the differing emphasis on interpersonal skills within the educational frameworks of Italian and Portuguese institutions, highlighting opportunities for cross-border knowledge exchange and the sharing of best practices. The findings underscore the potential of gamification in bridging the divide between theoretical knowledge and the practical application of skills, cultivating an interactive and supportive learning environment. Recommendations include systematically integrating interpersonal skills training, promoting inclusive learning environments, and strengthening partnerships between universities and industries.